The Relevance of the Theory of Legal Change According to Ibnu Qayyim Al-Jauziyyah in Legal Products by Fatwa DSN-MUI Indonesia - Muhamad Izazi Nurjaman; Doli Witro (El-Mashlahah, 2021)
ABSTRACTThe study described the relevance of the theory of legal change according to Ibnu Qayyim al-Jauziyyah to the legal product of the fatwa DSN-MUI (Fatwa National Sharia Board-Indonesian Council of Ulama) in Indonesia. It used a qualitative research method with a literary approach. The conclusions showed that the relevance of the theory of legal change proposed by Ibn Qayyim al-Jauziyyah has been applied explicitly in every legal product of the fatwa DSN-MUI in Indonesia. That seen in every legal product, always give the way for future changes following the needs and problems faced. Changes to Islamic legislation products have significant differences. On laws and regulations and judges' decisions, new legal products will cancel or revoke the previous legal. And, for the legal product of a fatwa from the National Syari'ah Board (DSN-MUI), the newly legal product will complete the previous one. However, legal changes will always occur in the context of providing legal certainty, accompanied by the level of benefit for people's lives.Keywords: Legal Changes, Ibn Qayyim, Products of Islamic Law.ABSTRAKPenelitian ini menjelaskan tentang relevansi teori perubahan hukum menurut Ibnu Qayyim al-Jauziyyah terhadap produk hukum fatwa DSN-MUI di Indonesia. Artikel ini menggunakan metode penelitian kualitatif yang bersifat kepustakaan. Hasil penelitian menunjukkan bahwa relevansi teori perubahan hukum yang digaungkan oleh Ibnu Qayyim al-Jauziyyah sudah diberlakukan secara eksplisit dalam setiap produk hukum fatwa DSN-MUI di Indonesia. Hal itu dapat dilihat dalam setiap batang tubuh produk hukum yang selalu membuka jalan untuk adanya perubahan dikemudian hari sesuai dengan kebutuhan dan problematika yang dihadapi. Perubahan terhadap produk hukum Islam memiliki perbedaan yang signifikan. Bagi peraturan perundang-undangan dan putusan hakim, ketentuan hukum baru akan membatalkan/mencabut ketentuan hukum sebelumnya. Sedangkan terhadap ketentuan hukum berupa fatwa Dewan Syari’ah Nasional (DSN-MUI), ketentuan hukum baru akan menyempurnakan ketentuan hukum sebelumnya. Namun sejatinya perubahan hukum akan selalu terjadi dalam rangka menciptakan produk hukum yang dapat memberikan kepastian hukum disertai pencapaian tingkat kemaslahatan bagi kehidupan masyarakat.Kata Kunci: Perubahan Hukum, Ibnu Qayyim, Produk Hukum Islam.